Analisis Sistem Agribisnis Rumput Laut di Kabupaten Takalar Provinsi Sulawesi Selatan - Nur Fatonny; Rita Nurmalina; Anna Fariyanti (Forum Agribisnis, 2023)
Seaweed is one of the most potential commodities in Indonesia which demand tends to increase overtime. Takalar Regency is the main producer of seaweed in South Sulawesi Province and has considerable resource potential in the fisheries sector. This study attempts analyzes portrait of the seaweed agribusiness system strarting from: the upstream subsystem, on-farm subsystem, processing subsystem, marketing subsystem, and supporting subsystem. The analysis used is descriptive, farming analysis, and analysis of the added value of the Hayami method. Determination of respondents using simple random sampling consisting of 33 seaweed cultivators and marketing actors consisting of seven collectors, two wholesalers, one exporter and one processing industry. The results showed that the seaweed agribusiness system still faces problems in both the upstream and downstream subsystems in cultivation equipment that is not environmentally friendly, seed quality, decreased production volume, capital, and institutional roles. Seaweed cultivation is profitable to cultivate with an R /C ratio 2,3. The added value ratio of dodol seaweed is 62.1%, seaweed jam 44,9% and Semi-Refined Carrageenan (SRC) 30,8%. There are five patterns of marketing channels formed from seaweed marketing activities. Seaweed business institutions consist of cultivator groups and cooperatives, and there is a Badan Usaha Milik Desa located in Laikang Village.